The Portuguese revolution of 1974-75 : an unexpected path to democracy - Rezola, Maria Inácia (Portuguese-speaking world (Series), 2023)
As Portugal is celebrating the 50th anniversary of the Carnation Revolution, this book conveys a global and differentiating perspective on the aims and actions of its three main protagonists - the Armed Forces, the political parties and mass social organizations - by close examination of original archival documentation; oral and written primary sources; and government records.